Evaluation of Sialyl-Lactotetra as a Marker for Epithelial Ovarian Tumors - Barone, Angela; Linder, Anna; Mateoiu, Constantina; Köster Larsen, Rasmus; Blixt, Ola; Teneberg, Susann; Sundfeldt, Karin (Frontiers in Oncology, 2020)
Ovarian carcinoma is a heterogeneous disease with distinct molecular and histological profiles, ranging from low grade atypia to highly aggressive tumors associated with a poor prognosis. In the present study, glycosphingolipids were isolated from human high-grade serous ovarian carcinoma, whereby the novel stem cell marker Sialyl-lactotetra (S-Lc4) was characterized in two out of three cases. The presence and level of S-Lc4 was further evaluated immunohistochemically in a cohort of patients with ovarian tumors ranging from benign lesions to high grade serous carcinoma (n = 478). Its expression was assessed in association with tumor grade, stage, histology and survival. The data showed that S-Lc4 is most common and highly expressed in borderline type tumors and carcinomas with low levels of aggressiveness, such as mucinous, endometrioid and low grade serous. Accordingly, S-Lc4-positivity was associated with better disease-free survival. The expression of S-Lc4 was seemingly associated with lineage continuity and could be traced from premalignant lesions to carcinoma, suggesting inheritance by a stem cell lineage that gives rise to generally indolent tumors.